2016
DOI: 10.2118/178436-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Optimizing Jet-Mill-Bit Hydraulics in Horizontal Drilling

Abstract: Summary Efficient cuttings transport is a major challenge in horizontal drilling; one can use a new type of jet-mill bit to overcome the challenge fundamentally. However, currently, there is no available method for optimizing jet-mill-bit hydraulics, which restricts the jet-mill bit from being widely used. In this paper, on the basis of the high-pressure water-jet comminution and jet-pump theory, a basic performance model of the jet-mill bit is developed. Then, the optimal parameter model for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…This triggered an idea of comminuting the cuttings right after they are generated, thereby cuttings accumulation in horizontal drilling may be eliminated (Chen et al 2016b). Chen et al (2016a, b, and c) developed a type of jet mill bit (JMB); this tool proffers a promising solution to the cuttings accumulation problem in horizontal drilling by comminuting cuttings into dustlike scale right after the cuttings are generated in the bottom hole. As it is, the JMB provides a promising solution to catch two birds with one stone: not only enhancing cuttings transport efficiency but also improving ROP by depressuring at the bottom hole.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This triggered an idea of comminuting the cuttings right after they are generated, thereby cuttings accumulation in horizontal drilling may be eliminated (Chen et al 2016b). Chen et al (2016a, b, and c) developed a type of jet mill bit (JMB); this tool proffers a promising solution to the cuttings accumulation problem in horizontal drilling by comminuting cuttings into dustlike scale right after the cuttings are generated in the bottom hole. As it is, the JMB provides a promising solution to catch two birds with one stone: not only enhancing cuttings transport efficiency but also improving ROP by depressuring at the bottom hole.…”
Section: Introductionmentioning
confidence: 99%
“…As Chen et al (2016a) reported, the JMB is developed based on the jet comminution technique, in which particles can be broken into smaller ones instantly by high-speed impacts of these particles against a target. When comminution chamber and target are removed from the jet mill of the JMB, it is a jet pump.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximizing ROP to reduce drilling cost in oil and gas development is the permanent objective of drilling researchers [1][2][3][4]. Numerous methods have been developed for optimizing drilling parameters to maximize ROP, and they are similar to drill rate and drill-off tests in that they observe trends in performance and attempt to identify the founder point, which is the point at which the ROP is maximized [5].…”
Section: Introductionmentioning
confidence: 99%
“…Wells are considered as extended-reach wells (ERWs) when their horizontal displacement (HD) to true vertical depth (TVD) ratio are higher than 2.0 [1,2]. In recent years, the extended-reach wells envelope is continuously expanded (see Figure 1), and now it is not surprising to drill extended-reach wells with HD to TVD ratio greater than 6.0 or with HD longer than 30,000 ft [3][4][5][6][7]. Recently, the world's longest well at the Sea of Okhotsk was successfully drilled.…”
Section: Introductionmentioning
confidence: 99%